2011
DOI: 10.1007/s12046-011-0007-7
|View full text |Cite
|
Sign up to set email alerts
|

Application of response surface methodology for determining cutting force model in turning hardened AISI H11 hot work tool steel

Abstract: This experimental study is conducted to determine statistical models of cutting forces in hard turning of AISI H11 hot work tool steel (∼ 50 HRC). This steel is free from tungsten on Cr-Mo-V basis, insensitive to temperature changes and having a high wear resistance. It is employed for the manufacture of highly stressed diecasting moulds and inserts with high tool life expectancy, plastic moulds subject to high stress, helicopter rotor blades and forging dies.The workpiece is machined by a mixed ceramic tool (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 13 publications
1
40
0
Order By: Relevance
“…Respectively, their contributions are 0.07% and 0.09%. These results are close to those found in [13][14][15][16][17][18][19][20][21]. The difference is the hardness of machined steel, its chemical composition and its mechanical characteristics.…”
Section: Anova For F a F R And F Tsupporting
confidence: 89%
“…Respectively, their contributions are 0.07% and 0.09%. These results are close to those found in [13][14][15][16][17][18][19][20][21]. The difference is the hardness of machined steel, its chemical composition and its mechanical characteristics.…”
Section: Anova For F a F R And F Tsupporting
confidence: 89%
“…Compared to grinding operations, precision hard turning enabled relatively high material removal rate and flexibility and thus, became more attractive especially to automotive, bearing and hydraulic industries [1][2][3]. Huang et al presented a thorough review that discusses CBN tool material microstructure, encountered wear patterns and tool wear rate modeling under hard turning [4].…”
Section: Introductionmentioning
confidence: 99%
“…Arsecularatne et al [18] and Ding et al [19] chose an orthogonal test (OT) to study the effect of cutting parameters on cutting force, and demonstrated suitable cutting force models. Lalwani et al [20] and Fnides et al [21] used the RSM to study effects of various parameters on the cutting force and provided their prediction accordingly. These methods have distinct differences in their numbers of tests used: RSM used more experimental data than OT.…”
Section: The Second Cutting Stepmentioning
confidence: 99%